VAHAN TERYAN IN DIALOGUE WITH FYODOR SOLOGUB - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2019)
The author of this article attaches attention for the first time to a series of important facts, the detailed consideration of which provides an extended picture of significant and diverse contact links of the great Armenian poet of the XX century Vahan Teryan with the work of the outstanding representative of the Silver Age’s Russian literature Fyodor Sologub. The article draws parallels and sheds light for the first time on the appearance of the triolet form in Teryan’s poetry